Applying the Concept of Embeddedness in the Retail Internationalization: A Case Study of Japanese Convenience Store FamilyMart in China - Sulin, Chung (Journal of Applied Business and Economics, 2017)
This paper applies the embeddedness concept identified by Hess (2004) and the ‘Convenience Business Model (CBM)’ framework to demonstrate how FamilyMart embedded itself in the Chinese market in two stages. This was achieved through a combination of societal, network, and territorial embeddedness. We discover that FamilyMart China transferred the basic CBM concept during the entry stage, and focused mainly on its ‘background system’ by entering into joint ventures. This embeddedness was primarily network-related. In FamilyMart China’s growth and development stage, the focus shifted towards the CBM ‘front system’ to create value for its customers and its embeddedness was primarily territorial.